Polypropylene composite material as well as preparation method and application thereof
By using aluminum oxynitride and magnesium aluminum spinel fillers in polypropylene composite materials and combining toughener, the problems of large shrinkage, poor solvent resistance and low light transmittance are solved, and the comprehensive performance of high dimensional stability, solvent resistance and light transmittance are achieved, which is suitable for the preparation of automotive parts.
Patent Information
- Application Number
- CN202411915074.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-08
AI Technical Summary
The existing polypropylene composite materials have problems such as large shrinkage, poor solvent resistance and low light transmittance, which are difficult to meet the dimensional stability and aesthetic requirements of light-transmitting parts in the interior and exterior of automobiles.
Aluminum oxynitride and magnesium aluminum spinel are used as fillers, combined with toughening agents, and the material shrinkage rate is reduced through low linear expansion coefficient and isotropic characteristics, forming a physical barrier layer to improve solvent resistance, and improving light transmittance through fillers with specific particle sizes.
It realizes the high dimensional stability, solvent resistance and light transmittance of polypropylene composite materials, and is suitable for the preparation of automotive parts, especially the transparency requirements of spray paint after laser engraving.
Smart Images

Figure BDA0005206645180000051 
Figure BDA0005206645180000061 
Figure BDA0005206645180000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of polypropylene materials, and in particular relates to a polypropylene composite material and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) offers advantages such as low density, low cost, and easy processing. PP is a translucent polymer material with a light transmittance of approximately 50-80%. It is widely used in light-transmitting components for automotive interior and exterior trim. However, light-transmitting PP is inherently brittle and has poor toughness. Rubber-phase elastomers are often added to improve this toughness and brittleness. However, elastomers adversely affect the material's light transmittance, reducing it. Furthermore, currently available light-transmitting PP composites suffer from poor dimensional stability and high shrinkage, typically exceeding 1%. Large parts such as bumpers experience significant dimensional variation, clearly failing to meet assembly requirements and rendering them impractical for practical application. Therefore, current approaches to improving the material's dimensional stability include the addition of inorganic fillers or other modifications. However, the fillers' high density and poor compatibility with the matrix significantly reduce the material's light transmittance. Furthermore, existing transparent PP materials also suffer from poor solvent resistance. Especially after laser engraving the surface of a transparent polypropylene bumper, when painting, the primer will physically swell with the bumper substrate, resulting in serious whitening problems at the laser engraving location, which not only affects the overall aesthetics of the bumper, but also affects the light transmittance of the laser engraved pattern. Summary of the Invention
[0003] In view of the defects of the polypropylene materials involved in the above-mentioned prior art, such as large shrinkage, poor solvent resistance and low light transmittance, the present invention will provide a polypropylene composite material and its preparation method and application.
[0004] To achieve the above objectives, the following technical solutions are specifically included:
[0005] In one aspect, the present invention provides a polypropylene composite material comprising the following components in parts by weight:
[0006] 49-71 parts of polypropylene, 8-32 parts of filler, 4-31 parts of toughening agent, 0.4-1.1 parts of auxiliary agent, wherein the filler comprises at least one of aluminum oxynitride and magnesium aluminum spinel; and the average particle size of the filler is 2-5 μm.
[0007] In the polypropylene material of the present invention, at least one of aluminum oxynitride and magnesium aluminum spinel is used as a filler. Its low linear expansion coefficient and isotropy are utilized to cooperate with the toughening agent to reduce the shrinkage rate of the material and improve the dimensional stability of the material. At the same time, based on the physical barrier properties and chemical stability of the filler, a physical barrier layer is formed on the surface of the material to prevent chemical reagents from penetrating and swelling the toughening agent, thereby improving the material's solvent resistance and meeting the requirements for post-laser engraving painting. Furthermore, since aluminum oxynitride and magnesium aluminum spinel are both materials that transmit visible light, not only does the material's light transmittance not be significantly reduced, but because fillers of different particle sizes have different dispersibility in the system and different light scattering, refraction, or transmission effects, the inventors of the present invention have discovered that selecting a filler with an average particle size of 2-5 μm can significantly improve the material's light transmittance. Therefore, the polypropylene composite material of the present invention can comprehensively achieve high dimensional stability, solvent resistance, and light transmittance.
[0008] Preferably, the polypropylene composite material comprises the following components by weight: 50-70 parts polypropylene, 10-30 parts filler, 5-30 parts toughening agent, and 0.5-1 part additive, wherein the filler comprises at least one of aluminum oxynitride and magnesium aluminum spinel. Common polypropylene resins in the art can be used in the present invention, including but not limited to at least one of homopolymer polypropylene, random copolymer polypropylene, and block copolymer polypropylene.
[0009] Preferably, the melt flow rate (MFR) of the polypropylene tested at 230°C and 2.16 kg load according to ISO 1133-2011 is 19-55 g / 10 min, specifically 19 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, 55 g / 10 min, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range. The polypropylene of the present invention may specifically include but is not limited to copolymer polypropylene having a melt mass flow rate of 19-55 g / 10 min when tested at 230° C. and 2.16 kg load according to ISO 1133-2011, including but not limited to random copolymer polypropylene having a melt mass flow rate of 19-55 g / 10 min when tested at 230° C. and 2.16 kg load according to ISO 1133-2011, including but not limited to block copolymer polypropylene having a melt mass flow rate of 19-55 g / 10 min when tested at 230° C. and 2.16 kg load according to ISO 1133-2011.
[0010] The mass percentage of the polypropylene resin in the polypropylene composite material of the present invention is not less than 40%, more preferably not less than 50%, and even more preferably not less than 70%.
[0011] Preferably, the filler includes aluminum oxynitride and magnesium aluminum spinel, and the mass ratio of aluminum oxynitride and magnesium aluminum spinel is (5-14): (1-10). The mass ratio of aluminum oxynitride and magnesium aluminum spinel can be specifically 5:1, 5:5, 5:10, 10:1, 10:5, 14:1, 14:5, 14:10, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0012] Different fillers have different effects on the transmittance of polypropylene composites. The inventors of the present invention have found that, preferably, when aluminum oxynitride and magnesium aluminum spinel are compounded as fillers, the dimensional stability and transmittance of the polypropylene composite material will be better than using only aluminum oxynitride or magnesium aluminum spinel.
[0013] Preferably, the toughening agent includes at least one of ethylene butene copolymer, ethylene octene copolymer (POE), and hydrogenated styrene-butadiene block copolymer (SEBS).
[0014] Preferably, the toughening agent has a melt flow rate of 1-13 g / 10 min, as measured in accordance with ASTM D1238 at 190°C and a load of 2.16 kg, and can specifically be 1 g / 10 min, 3 g / 10 min, 6 g / 10 min, 9 g / 10 min, 12 g / 10 min, 13 g / 10 min, and the like, as well as specific values between the aforementioned values. Due to space limitations and for the sake of brevity, the present invention does not exhaustively enumerate the specific values within the aforementioned ranges. The toughening agent of the present invention is generally an elastomer. The inventors of the present invention have discovered that the toughening agent can significantly increase the toughness of polypropylene composites, cooperate with fillers, reduce shrinkage, and improve solvent resistance and light transmittance.
[0015] The present invention adopts the laser diffraction method to test the average particle size of the filler. The average particle size of the filler can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0016] Preferably, the auxiliary agent includes at least one of an antioxidant, a weathering agent, and a lubricant.
[0017] More preferably, the lubricant includes at least one of an amide lubricant and a stearic acid lubricant.
[0018] More preferably, the antioxidant includes at least one of a hindered phenol antioxidant and a phosphite antioxidant.
[0019] More preferably, the weathering agent includes at least one of o-hydroxybenzophenone, benzotriazole, salicylate, triazine, substituted acrylonitrile, and hindered amine light stabilizers.
[0020] In the present invention, other (functional) additives may be added as needed, including but not limited to antioxidants, weathering agents, lubricants, etc. Conventional antioxidants, weathering agents, and lubricants in the art can be used in the present invention to increase the functionality of the polypropylene composite material and improve the overall performance of the polypropylene composite material.
[0021] On the other hand, the present invention provides a method for preparing the polypropylene composite material, comprising the following steps: uniformly mixing the raw materials, and sequentially subjecting the raw materials to melt extrusion and granulation to obtain the polypropylene composite material.
[0022] Preferably, the temperature of the melt extrusion is 180-230°C.
[0023] In addition, the present invention also provides an automobile part prepared according to the polypropylene composite material, wherein the automobile part is processed by laser engraving and then spray-painting.
[0024] The polypropylene composite material of the present invention has high dimensional stability, solvent resistance and light transmittance, and is particularly suitable for preparing painted automobile parts such as automobile bumpers and ambient lights. It can not only meet the basic requirements for dimensional stability of large parts, but also meet the transparency requirements of painting after laser engraving.
[0025] Compared with the prior art, the present invention has the following beneficial effects: in the polypropylene composite material of the present invention, the filler and the toughening agent of specific particle size cooperate with each other to significantly improve the dimensional stability, solvent resistance and light transmittance of the polypropylene composite material, so that the polypropylene composite material has the comprehensive performance of high dimensional stability, solvent resistance and light transmittance. DETAILED DESCRIPTION
[0026] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below through specific examples. Unless otherwise specified, the components and raw materials used in the examples and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all the same.
[0027] (1) Polypropylene:
[0028] PP-1: SZ30S, melt mass flow rate 30g / 10min, Sinopec;
[0029] PP-2: H9018, melt mass flow rate 55g / 10min, Lanzhou Petrochemical;
[0030] PP-3: RP346R, melt mass flow rate 19g / 10min, CNOOC Shell;
[0031] (2) Transparent ceramic materials
[0032] Aluminum oxynitride 1: After sieving, the powder with an average particle size of 3μm was obtained, Dingli Technology;
[0033] Aluminum oxynitride 2: After sieving, the powder with an average particle size of 2μm was obtained, Dingli Technology;
[0034] Aluminum oxynitride 3: After sieving, the powder with an average particle size of 5μm was obtained, Dingli Technology;
[0035] Aluminum oxynitride 4: After sieving, the powder with an average particle size of 1μm was obtained, Dingli Technology;
[0036] Aluminum oxynitride 5: After sieving, the average particle size is 6μm, Dingli Technology;
[0037] Magnesium aluminum spinel: magnesium aluminum spinel (MgAl6O 10 ) single crystal substrate, after sieving and screening to obtain powder with an average particle size of 3 μm, Hubei Baoling Chemical Technology Co., Ltd.;
[0038] Alumina: After sieving, the powder with an average particle size of 3 μm was obtained from Qinghe County Ruijiang Metal Materials Co., Ltd.
[0039] (3) Toughening agent:
[0040] Toughener 1: Ethylene butene copolymer, POE 7447, melt mass flow rate 5 g / 10 min, Dow;
[0041] Toughener 2: ethylene butene copolymer, POE 7467, melt mass flow rate 1.2 g / 10 min, Dow;
[0042] Toughener 3: ethylene butene copolymer, POE 7256, melt mass flow rate 2 g / 10 min, Dow;
[0043] Toughener 4: ethylene octene copolymer, POE 8137, melt mass flow rate 13 g / 10 min, Dow;
[0044] Toughener 5: hydrogenated styrene-butadiene copolymer, SEBS 7551, melt mass flow rate 5g / 10min, Lee Chang-jung, Taiwan, China;
[0045] (4) Antioxidants:
[0046] Antioxidants: SONOX 1010 and SONOX 168 were commercially available in a mass ratio of 1:1.
[0047] (5) Lubricant: ethylene bisstearamide, commercially available;
[0048] (6) Weathering agent: Hindered amine light stabilizer T-81, commercially available.
[0049] Examples 1-17 and Comparative Examples 1-5
[0050] A polypropylene composite material, the preparation method of which comprises the following steps:
[0051] (1) Add the raw materials except the filler into a high-speed mixer according to the ratio of each raw material in Table 1-2 and mix thoroughly. Then add the mixed material into the extruder through the main feeding port;
[0052] (2) The transparent ceramic material is added through the side feed port, the aspect ratio of the extrusion screw is 36-48:1, and the material is extruded and granulated after mixing, melting, and homogenization. The extruder temperature is set to: 80-120°C in zone 1, 180-200°C in zones 2-5, and 200-230°C in other zones. After granulation, the polypropylene composite material is obtained.
[0053] Table 1
[0054]
[0055] Table 2
[0056] Group / weight Example 16 Example 17 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 PP-1 / / 60 60 60 60 60 PP-2 60 / / / / / / PP-3 / 60 / / / / / Magnesium aluminum spinel 5 5 / / 5 5 5 Aluminum Oxynitride 1 10 10 / / 10 / / Aluminum Oxynitride 4 / / / / / 10 / Aluminum Oxynitride 5 / / / / / / 10 Alumina / / / 15 / / / Toughener 1 10 10 10 10 / 10 10 antioxidants 0.2 0.2 0.2 0.2 0.2 0.2 0.2 lubricant 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Weathering agent 0.2 0.2 0.2 0.2 0.2 0.2 0.2
[0057] In order to verify the performance of the polypropylene composite material of the present invention, the polypropylene composite materials prepared in the examples and comparative examples were subjected to performance tests. The specific test methods and qualification standards are as follows:
[0058] (1) Solvent resistance: The polypropylene composite materials of the above examples and comparative examples were injection molded into 210×150 mm specimens according to conventional processes. The specimens were laser engraved on their surfaces and then subjected to solvent resistance tests with a transparent primer. The degree of whitening caused by the interaction between the specimens and the transparent primer was observed and graded into three categories: no whitening (A), slight whitening (B), whitening and swelling whitening (C). Grades of B and above were considered acceptable.
[0059] (2) Dimensional stability: The polypropylene composite materials of the above-mentioned examples and comparative examples were injection molded into rectangular samples of 200×50 mm (molded in the injection mold cavity) according to conventional processes and annealed at 90°C for 2 hours. The dimensional changes before and after annealing were measured with a vernier caliper to calculate the shrinkage rate and evaluate the dimensional stability. The smaller the shrinkage rate, the better the dimensional stability. The shrinkage rate was calculated as follows: 1-(L0-L) / L0×100%, where L0 is the length of the injection mold cavity (i.e., before annealing) and L is the actual length of the injection molded sample after annealing. A shrinkage rate of ≤1% was considered acceptable.
[0060] (2) Light transmittance: The polypropylene composite materials of the above examples and comparative examples were injection molded into 150×100×3 mm samples according to conventional processes. The light transmittance was tested with reference to GB / T 2410-2008 standard. A light transmittance of 50% or higher was considered acceptable.
[0061] Table 3
[0062]
[0063]
[0064] As shown in the above examples, the polypropylene composite material of the present invention exhibits no whitening or swelling defects after laser engraving and painting, exhibits a shrinkage rate of less than or equal to 1%, and exhibits a light transmittance of ≥50%. This demonstrates that the polypropylene composite material of the present invention exhibits excellent solvent resistance, dimensional stability, and light transmission.
[0065] In Examples 7, 4, 1, 5, and 6, the content of aluminum oxynitride gradually decreases (conversely, the content of magnesium aluminum spinel gradually increases). The solvent resistance grades of Examples 7, 4, 1, and 5 containing aluminum oxynitride are all A, while the solvent resistance grade of Example 6 without aluminum oxynitride is B. Comparing Examples 1 and 4-7 with Comparative Example 1, which does not contain either magnesium aluminum spinel or aluminum oxynitride fillers, it can be found that both magnesium aluminum spinel and aluminum oxynitride can improve the solvent resistance of the polypropylene composite material, and aluminum oxynitride improves solvent resistance to a greater extent. In addition, when Examples 1 and 4-7 are compared with Comparative Example 2, where only aluminum oxide is used as the filler, the effect of aluminum oxide as the filler on improving the solvent resistance of the system of the present invention is poor, failing to meet practical requirements. It can be seen that different types of fillers can also have a significant impact on the solvent resistance of the polypropylene composite material. Only when the system of the present invention uses at least one filler of magnesium aluminum spinel and aluminum oxynitride can it achieve relatively good solvent resistance and meet the solvent resistance requirements of laser engraving and post-painting.
[0066] As the content of aluminum oxynitride in Examples 7, 4, 1, 5, and 6 gradually decreases (on the contrary, the content of magnesium aluminum spinel gradually increases), the shrinkage of the polypropylene composite material first decreases and then increases. Comparing Examples 1 and 4-7 with the case of Comparative Example 1 without any of the fillers magnesium aluminum spinel and aluminum oxynitride, it can be found that magnesium aluminum spinel and aluminum oxynitride can both improve the dimensional stability of the polypropylene composite material, and aluminum oxynitride improves the dimensional stability to a greater extent. Moreover, when the two are compounded, the dimensional stability of the polypropylene composite material is better. Comparing Examples 1 and 4-7 with the case of Comparative Example 2 where the filler is only aluminum oxide, when aluminum oxide is used as a filler, the effect of improving the shrinkage rate of the system of the present invention is poor and cannot meet the actual requirements. It can be seen that different types of fillers will also have a significant impact on the shrinkage properties of the polypropylene composite material. Only when the system of the present invention uses at least one filler of magnesium aluminum spinel and aluminum oxynitride can better dimensional stability be achieved.
[0067] As the content of aluminum oxynitride in Examples 7, 4, 1, 5, and 6 gradually decreases (on the contrary, the content of magnesium aluminum spinel gradually increases), the light transmittance of the polypropylene composite material first increases and then decreases. Comparing Examples 1 and 4-7 with the case of Comparative Example 1 without any of magnesium aluminum spinel and aluminum oxynitride fillers, it can be found that magnesium aluminum spinel and aluminum oxynitride can both improve the light transmittance of the polypropylene composite material, and aluminum oxynitride improves the light transmittance to a greater extent. Moreover, when the two are compounded, the light transmittance of the polypropylene composite material is better. Comparing Examples 1 and 4-7 with the case of Comparative Example 2 where the filler is only aluminum oxide, when aluminum oxide is used as a filler, the effect of improving the light transmittance of the system of the present invention is poor and cannot meet the actual requirements. It can be seen that different types of fillers can also have a significant impact on the light transmittance of the polypropylene composite material. Only when the system of the present invention adopts at least one filler of magnesium aluminum spinel and aluminum oxynitride can a better light transmittance effect be achieved.
[0068] The average particle size of aluminum oxynitride gradually increased in Comparative Example 4, Example 2, Example 1, Example 3, and Comparative Example 5. The solvent resistance of Examples 1-3 and Comparative Example 5 all reached Grade A. However, the average particle size of the aluminum oxynitride in Comparative Example 4 was too small, resulting in poor physical barrier properties and failing to significantly improve the solvent resistance of the polypropylene composite material. As the average particle size of the aluminum oxynitride gradually increased, shrinkage initially decreased and then increased, but dimensional stability remained acceptable within an average particle size range of 1-6 μm. Transmittance initially increased and then decreased with increasing average particle size, but only within an average particle size range of 2-5 μm did the transmittance meet the requirements. Excessively small or large average particle sizes significantly reduced the transmittance of the material. Therefore, the present invention achieves both good solvent resistance and transmittance only when using fillers with an average particle size of 2-5 μm.
[0069] It can be seen from Examples 1 and 3 that the toughening agent can significantly improve the dimensional stability and light transmittance of the polypropylene composite material, and it can be seen from Examples 1 and 8-13 that the melt mass flow rate and type of the elastomeric toughening agent have little effect on the solvent resistance, dimensional stability, and light transmittance of the polypropylene composite material. However, the toughening agent content should not be too much. Excessive toughening agent will exceed the dispersion threshold of the system, resulting in poor physical barrier properties in the system and reduced solvent resistance and light transmittance.
[0070] Comparing Example 1 with Comparative Examples 1-3, it can be seen that in the system of the present invention, the lack of any one of the filler and the toughening agent cannot achieve a balance between solvent resistance, dimensional stability and light transmittance. Only when fillers and toughening agents of specific types and sizes are simultaneously present in the system can better solvent resistance, dimensional stability and light transmittance be achieved.
[0071] It can be seen from Examples 1 and 16-17 that the melt mass flow rate has little effect on the solvent resistance and dimensional stability of the polypropylene composite material. As the melt mass flow rate increases, the transmittance first increases slightly and then decreases slightly. Therefore, when the melt mass flow rate is 19-55 g / 10 min, the transmittance of the polypropylene composite material is better.
[0072] In summary, the present invention introduces magnesium aluminum spinel and / or aluminum oxynitride into transparent ceramics to cooperate with the elastomer toughening agent, utilizing the low linear expansion coefficient and isotropy of such transparent ceramics, as well as the toughening agent's ability to increase the compatibility and toughness of the system, to reduce the post-shrinkage of the polypropylene composite material and solve the problem of dimensional stability of large parts such as translucent bumpers. By virtue of the physical barrier properties and good chemical stability of magnesium aluminum spinel and / or aluminum oxynitride of a specific particle size, a physical barrier layer is formed on the surface of the polypropylene composite material during injection molding, preventing chemical reagents from penetrating and swelling the elastomer toughening agent in the polypropylene composite material, thereby improving solvent resistance. In addition, since aluminum oxynitride and magnesium aluminum spinel are both materials that can transmit visible light, not only will the light transmittance of the material not be significantly reduced, but also, since fillers of different particle sizes have different dispersibility, scattering, refraction or transmission effects on light in the system, the present invention can maintain the high light transmittance of the polypropylene composite material when using magnesium aluminum spinel and / or aluminum oxynitride with an average particle size of 2-5 μm.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A polypropylene composite material, characterized in that: The composition comprises the following components in parts by weight: 49-71 parts of polypropylene, 8-32 parts of filler, 4-31 parts of toughening agent, 0.4-1.1 parts of auxiliary agent, the filler comprises at least one of aluminum oxynitride and magnesium aluminum spinel; the average particle size of the filler is 2-5 μm.
2. The polypropylene composite material according to claim 1, characterized in that The filler comprises aluminum oxynitride and magnesium aluminum spinel, and the mass ratio of aluminum oxynitride to magnesium aluminum spinel is (5-14): (1-10).
3. The polypropylene composite material according to claim 1, characterized in that: The toughening agent includes at least one of ethylene butene copolymer, ethylene octene copolymer and hydrogenated styrene-butadiene block copolymer.
4. The polypropylene composite material according to claim 1, characterized in that: The toughening agent is tested according to ASTM D1238 at 190° C. and 2.16 kg load and has a melt mass flow rate of 1-13 g / 10 min.
5. The polypropylene composite material according to claim 1, characterized in that: The polypropylene has a melt mass flow rate of 19-55 g / 10 min when tested at 230° C. and 2.16 kg load according to ISO1133-2011.
6. The polypropylene composite material according to claim 1, characterized in that: The auxiliary agent includes at least one of an antioxidant, a weathering agent, and a lubricant.
7. The polypropylene composite material according to claim 6, characterized in that: The antioxidant includes at least one of hindered phenol antioxidants and phosphite antioxidants; the lubricant includes at least one of amide lubricants and stearic acid lubricants; the weathering agent includes at least one of o-hydroxybenzophenone, benzotriazole, salicylate, triazine, substituted acrylonitrile, and hindered amine light stabilizer.
8. A method for preparing the polypropylene composite material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: uniformly mixing various raw materials, sequentially subjecting the raw materials to melt extrusion and granulation to obtain the polypropylene composite material.
9. An automobile part prepared according to the polypropylene composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polypropylene material applied to automobile and production method of polypropylene material
CN109517269A
Sand-plastic composite material with effect of releasing negative ions and preparation method of sand-plastic composite material
CN109776903A
Composition with thermal conductivity and laser plating performance by core-shell structure lds additive with metal compounds coated on mineral filler surface
CN110300778A
High-toughness conductive nylon material and preparation method thereof
CN114685976A
Aluminum nitride / needle-shaped aluminum oxide filled cold-touch polypropylene composite material and preparation method thereof
CN116874929A